Proceedings of the Second International Conference on Performance-Based and Life-Cycle Structural Engineering (PLSE 2015) 2015
DOI: 10.14264/uql.2016.544
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies of gypsum plasterboard and MgO board lined LSF walls exposed to fire

Abstract: Fire resistance of cold-formed light gauge steel frame (LSF) wall systems is enhanced by lining them with single or multiple layers of wall boards with varying thermal properties. These wall boards are gypsum plasterboards or Magnesium Oxide (MgO) boards produced by different manufacturers. Thermal properties of these boards appear to show considerable variations and this can lead to varying fire resistance levels (FRL) for their wall systems. Currently FRLs of wall systems are determined using full scale fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…shown in Figure 3, the first two peaks occurred at about 180-230 °C, the third and fourth peaks occurred at 400-475 °C, and the last peak occurred at about 520 °C [53]. According to Rusthi et al [52,54], the first two peaks were due to dehydration of magnesium oxychloride and evaporation of water, the third and fourth were due to hydrolysis and pyrolysis, and the last peak was due to the release of chemically bound water. Although the boards have an advantage over GB and OSB panels in terms of acoustic properties, the authors concluded that the main disadvantage of this type of boards is that they have a very high mass loss at elevated temperatures, about 15% higher compared to GBs.…”
Section: Sheathing Boards and Finishing Layersmentioning
confidence: 90%
“…shown in Figure 3, the first two peaks occurred at about 180-230 °C, the third and fourth peaks occurred at 400-475 °C, and the last peak occurred at about 520 °C [53]. According to Rusthi et al [52,54], the first two peaks were due to dehydration of magnesium oxychloride and evaporation of water, the third and fourth were due to hydrolysis and pyrolysis, and the last peak was due to the release of chemically bound water. Although the boards have an advantage over GB and OSB panels in terms of acoustic properties, the authors concluded that the main disadvantage of this type of boards is that they have a very high mass loss at elevated temperatures, about 15% higher compared to GBs.…”
Section: Sheathing Boards and Finishing Layersmentioning
confidence: 90%
“…They possess high strength-to-weight ratio, better durability, enhanced thermal comfort and are easy to install [2]. However, this material does not deliver enough thermal resistance to fulfil the stringent insulation regulations.…”
Section: Plaster-nanofiller Compositementioning
confidence: 99%
“…In developed countries, the LSF (Light Steel Framing) constructive system is widely used in different architectural typologies. It consists of cold formed galvanized steel profiles, whose mechanical performance is satisfactory, besides presenting acceptable durability and aesthetic standard in the civil construction scenario; in terms of cost/benefit, in relation to the other structural systems designed in steel, it offers real advantages [2]. The LSF constructive system is characterized by being composed of lightweight profiles, disposed in a submultiple structural modulation of the dimensions of the plates that make the panels closures and in an integrated way produce self-supporting elements that support walls, floors and roofs.…”
Section: Introduction mentioning
confidence: 99%